NEURO-FUZZY-INTEGRAL MODEL FOR HOLISTIC EVALUATION OF AN URBAN MAGNETIC LEVITATION TRANSPORTATION SYSTEM - Sucena, Marcelo Prado; Stephan, Richard Magdalena; Junior, Vicente Almeida (Brazilian Journal of Operations & Production Management, 2013)
<span style="font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; letter-spacing: -.05pt; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">Nowadays, the management of industries or services must respect the principles of sustainability. The various aspects involved, inherent in the production of goods or facilities and in the environment, should be considered. An Environmental Management System (EMS) allows planning, organizing and carrying out the operational and environmental actions in a methodical and effective way. With reference to the implementation of an urban magnetic levitation transportation system, called MagLev-Cobra, this paper proposes a model of EMS, which results in the establishment of a Systemic Sustainability Indicator (SSI). This tool provides a simple but rigorous and objective method to analyze, compare and evaluate the impacts of the project under the principles of sustainability. Concepts of Fuzzy Theory and Neural Networks were applied to obtain the SSI, which brings together the environmental indicators proposed in the EMS of the MagLev-Cobra system, allowing a holistic evaluation.